Impact of Comorbid Prematurity and Congenital Anomalies: A Review - Gunn-Charlton, Julia K. (Frontiers in Physiology, 2022)
Preterm infants are more likely to be born with congenital anomalies than those who are born at full-term. Conversely, neonates born with congenital anomalies are also more likely to be born preterm than those without congenital anomalies. Moreover, the comorbid impact of prematurity and congenital anomalies is more than cumulative. Multiple common factors increase the risk of brain injury and neurodevelopmental impairment in both preterm babies and those born with congenital anomalies. These include prolonged hospital length of stay, feeding difficulties, nutritional deficits, pain exposure and administration of medications including sedatives and analgesics. Congenital heart disease provides a well-studied example of the impact of comorbid disease with prematurity. Impaired brain growth and maturity is well described in the 3rd trimester in this population; the immature brain is subsequently more vulnerable to further injury. There is a colinear relationship between degree of prematurity and outcome both in terms of mortality and neurological morbidity. Both prematurity and relative brain immaturity independently increase the risk of subsequent neurodevelopmental impairment in infants with CHD. Non-cardiac surgery also poses a greater risk to preterm infants despite the expectation of normal in utero brain growth. Esophageal atresia, diaphragmatic hernia and abdominal wall defects provide examples of congenital anomalies which have been shown to have poorer neurodevelopmental outcomes in the face of prematurity, with associated increased surgical complexity, higher relative cumulative doses of medications, longer hospital and intensive care stay and increased rates of feeding difficulties, compared with infants who experience either prematurity or congenital anomalies alone.